Teaching ability development through professional learning community : A case study of teacher for local development project on induction period in Thailand - Janjang, Siriwan; Vetsawat, Chanarak; Pariput, Pariya; Panyapa, Rattana (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
In Thailand, the Teachers Council has implemented the Teachers for Local Development Project. This research is part of the teacher development process in the said project. It was found that 1) factors in developing teachers' teaching ability through professional learning communities included motivation for self-development, 5 components of desirable professional learning communities: role models, administrators, buddy teachers, mentors, and experts; 2) The results with students were as follows: 2 students had performance at a good level, 8 students had performance at a moderate level, and 5 students had performance at a fair level; the results for teachers were found that teachers were empowered and suggested for self-development in terms of analyzing learners and managing individual learning, specifying clear expected learning outcomes, practicing basic skills, using technology as a base, using situations, using questions, using games, applying in real life, practicing, creating a democratic atmosphere for learning, developing a learning ecosystem for lifelong learning; the results for schools and communities were found that there was a professional learning community by exchanging knowledge and suggestions as a guideline for participatory development.